Mechanisms underlying the therapeutic effects of 4-octyl itaconate in treating sepsis based on network pharmacology and molecular docking - Chen, Maolin; Su, Wenxing; Chen, Fangling; Lai, Tianlun; Liu, Yilun; Yu, Daojiang (Frontiers in Genetics, 2022)
Objective: Through network pharmacology and molecular docking technology, the hub genes, biological functions and signalling pathways of 4-octyl itaconate against sepsis were revealed. Methods: Pathological targets of sepsis were screened using GeneCards and GEO databases. Similarly, the pharmacological targets of 4-OI were obtained through Swiss TargetPrediction (STP), Similarity ensemble approach (SEA) and TargetNet databases. Then, all the potential targets of 4-OI anti-sepsis were screened by the online platform Draw Venn diagram, and the hub genes were screened by Cytoscape software. The identified hub genes were analyzed by GO and KEGG enrichment analysis, protein interaction (PPI) network, and molecular and docking technology to verify the reliability of hub gene prediction, further confirming the target and mechanism of 4-OI in the treatment of sepsis. Results:  After the target screening of 4-OI and sepsis, 264 pharmacological targets, 1953 pathological targets and 72 genes related to 4-OI anti-sepsis were obtained, and eight hub genes were screened, namely MMP9, MMP2, SIRT1, PPARA, PTPRC, NOS3, TLR2 and HSP90AA1. The enrichment analysis results indicated that 4-OI might be involved in the regulation of inflammatory imbalance, immunosuppression and oxidative stress in the development of sepsis. 4-OI protects multiple organ dysfunction in sepsis by acting on hub genes, and MMP9 is a reliable gene for the prognosis and diagnosis of sepsis. The molecular docking results showed that 4-OI binds well to the hub target of sepsis. Conclusion: 4-OI plays an antiseptic role by regulating MMP9, MMP2, SIRT1, PPARA, PTPRC, NOS3, TLR2 and HSP90AA1. These Hub genes may provide new insights into follow-up research on the target of sepsis treatment.